Pengaruh Financial Technology terhadap Ukuran Perusahaan pada Perbankan Syariah Indonesia yang Terdaftar di BEI - Nisa Wildaningrum Saputri; Tinneke Hermina; Uu Suparman (Jurnal Wahana Akuntansi, 2025)
This study aims to analyze the relationship between financial technology (fintech) services and firm size in Islamic banking in Indonesia. The research method used is a descriptive method with a quantitative approach. The data used are secondary data obtained from the financial statements and annual reports of Islamic banks listed on the Indonesia Stock Exchange (IDX) for the period 2017–2021, particularly the financial position statements in the balance sheet accounts. Data analysis was conducted using simple linear regression analysis. Data collection was carried out through the documentation method. The results of the study show that the number of fintech services in three Islamic banks increased from four types of services in 2017–2019 to five types of services in 2020–2021. This increase in fintech services was followed by an increase in the total assets of the companies each year. The average value of total assets reached IDR 8,757,978,851, with a minimum value of IDR 661,912,000 at Bank Aladin Syariah in 2018 and a maximum value of IDR 18,543,856,000 at Bank BTPN Syariah in 2021. These findings indicate that the increase in fintech services contributes to the growth of firm size and reflects improving financial conditions.